2020
DOI: 10.25259/jcis_36_2020
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Cardiac Output with Phase Contrast Magnetic Resonance Imaging in Patients with Pulmonary Hypertension

Abstract: Objective: The purpose of the study is to compare phase contrast (PC) imaging with invasive measurements of cardiac output (CO) in patients with pulmonary hypertension (PH). Materials and Methods: We analyzed 81 cases with PH who underwent cardiac magnetic resonance imaging and right heart catheterization (RHC). Measurement of CO and stroke volume (SV) by cardiac magnetic resonance (CMR) was performed by PC imaging of the proximal aorta (Ao) and pulmonary artery (Pa) and by RHC using the Fick and thermodilut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…Therefore, in our population, SV MRI cannot be considered interchangeable with the reference SV TD method. This is concordant with previous results in the field showing a wide range of the 2SD of bias (ranging from 1.9 L/min to 2.4 L/min) and PE when comparing MRI with TD [ 24 , 25 , 26 , 27 ]. As aforementioned, the LoA and PE are the results of the imprecision of the two studied methods.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, in our population, SV MRI cannot be considered interchangeable with the reference SV TD method. This is concordant with previous results in the field showing a wide range of the 2SD of bias (ranging from 1.9 L/min to 2.4 L/min) and PE when comparing MRI with TD [ 24 , 25 , 26 , 27 ]. As aforementioned, the LoA and PE are the results of the imprecision of the two studied methods.…”
Section: Discussionsupporting
confidence: 93%
“…In this context, it is likely that TD might be the cause of the lack of agreement when we compared TD with MRI. This would also explain the constant lack of agreement between CO MRI and CO TD in other studies in this field, while a good agreement between SV AAO and SV RV was demonstrated against the gold standard SV DF [ 19 , 24 , 25 , 26 , 27 ]. In our study, the delay between MRI and TD could also contribute to lower the observed agreement between MRI and TD due to change in the haemodynamic condition of the patients.…”
Section: Discussionmentioning
confidence: 97%
“…Also, a recent publication in 2020 demonstrated that CI measured by 2D flow (Ao and Pa) showed a low correlation with CI measured invasively. The correlation coefficients were similar to our results among the different comparisons of CI: PC‐Fick (Ao r = 0.70, Pa r = 0.67) 19 …”
Section: Discussionsupporting
confidence: 89%
“…16,17 In contrast, it has been demonstrated that CI measured by 2D flow (aorta and pulmonary) in patients with PH had a low agreement with CI measured invasively. 18,19 2D flow measures flow only in one direction perpendicular to the blood vessel. [10][11][12][13][14][15] Pulsatile blood flow through the great vessels is multidirectional and multidimensional.…”
Section: Introductionmentioning
confidence: 99%
“…So, what could be other possible explanations for the differences in the findings between this study and previous studies? First, the 3 studies used different methods of measuring the CO: This study used phase contrast magnetic resonance imaging to quantify macrovascular flow, which has been found to be comparable with the invasive technique of right heart catheterization using the Fick principle and thermodilution method (14). The authors' own previous study used gated myocardial scintigraphy with single-photon emission computed tomography, which has been shown to underestimate the CO (12).…”
mentioning
confidence: 99%